PENGARUH RASIO PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SUB INDUSTRI TEKSTIL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yolanda, Miadiarti; Rismansyah, Rismansyah; Sudiyanto, Totok (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Financial distress is a condition in which the company experiences financial difficulties before being in a state of bankruptcy. This study aims to obtain empirical evidence on the effect of profitability, liquidity, and leverage ratios on financial distress in textile subsector companies listed on the Indonesia Stock Exchange between 2017-2021. This study uses quantitative methods with descriptive and associative approaches and uses binary logistic regression analysis methods. The sample used amounted to 10 companies with an observation period of 5 years with 50 data as a research sample. Partially, the profitability ratio proxied by ROA and the liquidity ratio proxied by CR affect financial distress. While partially the leverage ratio proxied by DER does not affect financial distress. Simultaneously, financial distress for textile companies trading on Indonesia's stock exchange is affected by profitability ratios derived from ROA, liquidity ratios derived from CR, and leverage ratios derived from DER. Keywords: Profitability; Liquidity; Leverage; Financial Distress